Cytotoxicity and molecular-docking approach of a new rosane-type diterpenoid from the roots of Euphorbia nematocypha - Song, Nali; Zheng, Xi; Wang, Jiapeng; Zhu, Li; Wang, Chengyao; Cai, Le; Ding, Zhongtao (Frontiers in Chemistry, 2022)
A new rosane-type diterpenoid (1) along with nine known diterpenoids (2–10) were isolated from the dried roots of Euphorbia nematocypha. The absolute configuration was elucidated from spectroscopic (nuclear magnetic resonance, high-resolution electrospray ionization mass spectrometry, and electronic circular dichroism) and optical-rotation analyses. Cytotoxicity and the ability to scavenge 2,2-diphenyl-1-picrylhydrazyl radicals were determined. Compound 1 showed remarkable cytotoxicity against human cancer cell lines (HeLa, CT26, and HCC1806) in vitro. The interaction between compound 1 and proteins of ribosomal S6 kinase were revealed using molecular docking, and provided valuable insights into the cytotoxic mechanism of action of Compound 1. The latter could be developed as a pharmaceutical agent in the future.